Aspects of Obstacles to the Implementation of Restitution for Victims of Traffic Accidents Causing Death - Zulkifli S Alintiq (Universitas Negeri Gorontalo, 2022)
The purpose of this research is to know and analyze about kObstacles in the implementation of restitution for victims of traffic accidents that cause death are;Legal procedures and processes are long and complicated, law enforcement is not involved in the implementation of restitution, which means that the police do not intervene in determining compensation costs, the majority of people do not know that there is compensation in the form of restitution that must be given to perpetrators outside of the criminal cases they receive and factors perpetrators who are unable to pay compensation. By him, the researcher suggests that the police play an active role in providing socialization to the community regarding the rights they receive when they become victims of traffic accidents, especially the existence of a merger of cases with claims for compensation and law enforcers should facilitate the process of submitting requests related to compensation (restitution), by accelerating settlement of criminal cases experienced by victims in the trial process.